Results of optimization of technological parameters for aaruul drying equipment (Mongolian Journal of Agricultural Sciences, 2024)
Mongolia has a large nomadic culture which has existed for thousands of years. Nomadic herders spend much of their time producing milk and dairy products, including Aaruul, or dried yogurt curd, which is a local dairy product unique to Mongolia. A drying device was designed to dry aaruul made by traditional methods to a moisture content no more than 20% in a short period of time, and the optimum values of drying temperature, drying time, and air flow speed were determined by multi-factored model and step-by-step decomposition method. As a result of the experiment, curd with a moisture content of 60% is dried at a temperature of 440C with an air flow speed with 3m/s for 7 hours, and the moisture content becomes 19.8%. It takes 4-5 days to dry curd naturally, and by using this device, curd drying time can be reduced by 10-17 times and the productivity of curd production can be increased. The electricity consumption of the device for drying 1kg of curd is 1.5 kWh.